Development of a self-evaluation scale of nursing practices for improving sleep quality among dementia patients taking sleeping pills - Yuichi Iwamoto; Narumi Fujino; Takaomi Furuno; Yuji Fujimoto (Tehran University of Medical Sciences, 2023)
Background & Aim: Many patients with dementia experience sleep-related issues. However, the nursing practices that address those issues are unclear. Therefore, to develop a self-assessment scale of nursing practices to improve sleep quality in patients with dementia taking sleep medication and confirm its validity and reliability. Methods & Materials: In this mixed-methods study, qualitative research was conducted by interviewing six expert-level nurses with a wealth of experience in caring for patients with dementia; then, quantitative survey questions were administered. The preliminary scale was created and evaluated its face validity. This quantitative study was conducted using questionnaire surveys among nurses with psychiatric ward experience employed at dementia treatment centers across Japan. Data from 525 nurses were used to verify the validity and reliability of the scale. Results: Exploratory factor analysis resulted in a three-factor, 16-item scale. Criterion validity was confirmed by calculating correlation coefficients with existing scales (the self-evaluation scale of oriented problem-solving behavior in nursing practice) as external criteria (r= 0.574, p< .05). The sum of scale scores and Cronbach's α coefficients for the three factors all exceeded 0.7. Conclusion: The development of this scale will improve the quality of nursing practice for patients with dementia who take sleeping pills. Additionally, it provides foundational research on nursing practice for the appropriate use of medications, as it offers evidence that nurses participate in drug treatment.